Review on NSAIDs: Frequently Used Drugs with Underlying Risks (Bangladesh Pharmaceutical Journal, 2012)
Analgesics and non-steroidal anti-inflammatory drugs (NSAIDs) are among the most widely used therapeutic agents today. An estimated 35 million or more people take traditional analgesic drugs regularly. But the presence of microscopic gastrointestinal bleeding is almost universal in patients treated with NSAIDs. Available reports and surveys reveal that thousands of people die every year due to GI perforation; many more suffer from peptic ulceration. The origin of these GI complications (nausea, heartburn, indigestion and abdominal pain, ulcers, perforation, bleeding etc.) is grafted with how NSAIDs works to reduce pain and inflammation. As a number of NSAIDs are available over-the-counter (OTC), many patients inappropriately assume that these are harmless and pose no risks because they are available without prescription. The objective of this review is to shed light on the risks associated with NSAIDs and to minimize the potential harmful effects to the patients. The review covers the development history of NSAIDs, their mechanism of action, allied adverse effects, present market scenario and steps to improve patient safety. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12591 Bangladesh Pharmaceutical Journal 15(2): 187-191, 2012